2017
DOI: 10.1097/mnm.0000000000000612
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-weighted MRI and 18F-FDG-PET/CT imaging

Abstract: Both DWI-MRI and F-FDG-PET/CT have their own advantages, and should be performed in a 'one stop shop' scan in the near future by PET/MRI engines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…DWI and FDG-PET/CT have their own advantages [35]. DWI provides quantitative information regarding tissue cellularity and the diffusion of water molecules which are not necessarily related to cancer aggressiveness.…”
Section: Discussionmentioning
confidence: 99%
“…DWI and FDG-PET/CT have their own advantages [35]. DWI provides quantitative information regarding tissue cellularity and the diffusion of water molecules which are not necessarily related to cancer aggressiveness.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Nakajo et al [ 24 ] and Choi et al [ 25 ] mentioned that SUVmax and ADC correlated with several pathological prognostic factors and both indexes may have the same potential for predicting the prognosis of breast cancer. DWI-MRI and FDG-PET/CT have their own advantages [ 26 ]. Gallivanone et al [ 27 ] reported that FDG-PET predicts patient prognosis and DWI predicts response to neoadjuvant chemotherapy, and both examinations provide useful complementary information for biological characterization and neoadjuvant chemotherapy response prediction in breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Another potential clinical impact of our study is related to the number of MRI assessments in cases of doubtful findings in the ultrasound assessment of reportedly uterine myomas. MRI is considered a good imaging technique for differentiating benign myomas from malignant sarcomas [32,33]. Typical findings for uterine leiomyosarcomas in MRI are high signals in T2WI, abnormal signals in DWI, high signals in T1WI, and ill-defined tumor mass borders [33].…”
Section: Discussionmentioning
confidence: 99%